Applications of fuzzy logic to reconfigure human resource management practices for promoting product innovation in formal and non-formal R&D firms - Tieng Kimseng; Amna Javed; Chawalit Jeenanunta; Youji Kohda (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Human resource management (HRM) practices for promoting innovation tend to vary from one context to another. This leads us to investigate the configurations of internal HRM practices and supply chain collaborations that help firms to achieve high levels of product innovation or cause firms to achieve low levels of product innovation in formal R&D firms-firms which have actively engaged in systematic innovation, have established an R&D department, and/or have allocated budgets for R&D intention-and non-formal R&D firms. The data were collected during the period December 2016-February 2017 from manufacturing firms located in the Bangkok metropolitan area, Thailand. In total, 87 respondents were included for an empirical fuzzy-set qualitative comparative analysis. The results indicate that, first, formal and non-formal R&D firms achieve high levels of product innovation by adopting internal HRM practices or collaborating with customers/suppliers. They also can achieve high levels of product innovation if they adopt both simultaneously. Second, formal R&D firms achieve high levels of product innovation if they adopt R&D personnel development; otherwise, they need to collaborate with customers and suppliers to achieve high levels of product innovation. Finally, miss-adopting R&D personnel development causes formal and non-formal firms to achieve lows levels of product innovation.
Keywords: 650; fuzzy-set qualitative comparative analysis; internal HRM practices; product innovation; supply chain collaboration; technological capabilities